If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 2p = 6 Solving 2 + 2p = 6 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 2p = 6 + -2 Combine like terms: 2 + -2 = 0 0 + 2p = 6 + -2 2p = 6 + -2 Combine like terms: 6 + -2 = 4 2p = 4 Divide each side by '2'. p = 2 Simplifying p = 2
| 168/x=12 | | 9x-3y=-81 | | 3h^2+10h-8=0 | | n-15=31 | | 104=2v^2+8 | | x+5=4x-13 | | 12=2L+(10) | | 56=w^2+6 | | 0.25x+0.2y=350 | | 988()=1234 | | x(x+5)=-150 | | x+7=3-x | | 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 | | 5y+6=-y+24 | | 42-14x=-5(6x+2)-5(-8-3x) |